A Seamless Handover Scheme With Assisted eNB for 5G C/U Plane Split Heterogeneous Network - Ziyang Zhang; Zhao Junhui; Shanjin Ni; Yi Gong (IEEE Access, 2019)
Considering the frequent handover problem caused by network densification and the employment of millimeter wave (mmWave) in 5G heterogeneous networks (HetNets), we present a novel network framework for 5G control/user plane split (CUPS) network to perform seamless handover between two neighbour macro evolved nodeBs (M-eNBs). By introducing an eNB called handover assisted micro eNB (HO A-eNB) in the overlapping region, the success probability of the handover between two M-eNBs can be significantly improved. When a user equipment (UE) is performing the inter M-eNBs handover, the UE will keep the dual connectivity with the source M-eNB and the HO A-eNB. After the handover is completed, UE will keep connecting with the HO A-eNB and the former target M-eNB. By introducing HO A-eNB and redesigning the signaling procedure of inter M-eNBs handover, we can obtain better handover performance, and the reliability of communication systems can be greatly enhanced. Simulation results show that the handover outage probability is lower than that of the traditional CUPS HetNets, and the handover success probability of inter M-eNB is almost 34.7% improved.